Birthing a Nation, Breaching the Border: Silvia Gruner's Mitad del Camino - Jamie L. Ratliff (Nierika, 2018)
In 1994, artist Silvia Gruner lined a section of the border between the U.S. and Mexico with ceramic replicas, representing Tlazoltéotl, the Aztec goddess of filth and purification. Entitled La mitad del camino, these figures allude to the liminality of a national boundary that is breached by passage through the abject female body, ironically referencing archetypal representations of women as bastions of maternity and domesticity, responsible for the reproduction and preparation, or rearing, of national citizens. Gruner modeled her Tlazoltéotls after the Dumbarton Oaks Birthing Figure, one of the most well-known pieces from the collection, which many have called a forgery. This paper argues that La mitad del camino critiques the ways that an intersecting discourse of gender, ethnicity, and memory has been exploited to theorize and construct Mexican nationhood, even in the face of its necessary moves toward globalization.